Observations on Italian sigillata: Ephesos - Martin, Archer (Rei Cretariae Romanae Fautorum Acta, 2024)
Material from consumption sites is most often studied with an eye to dating and patterns of importation. The observation of sherds excavated at consumption sites can, however, provide other information as well. The Italian sigillata (in particular plates and platters) from the Hanghäuser at Ephesos offers one example. The observations concern the fashioning, finishing and firing of vessels.